Dynamics of Intellectual Capital, Corporate Governance, and Firm Performance in Family-Owned Companies in Pakistan - Hassan Muhammad Shoaib; Ahmad Ashfaq; Qadeer Abdul (NUML International Journal of Business & Management, 2022)
The study aims to examine the corporate governance effect on the performance of family-owned cement companies in Pakistan for the period 2016 to 2021 using random and fixed effect panel regression based on the Hausman test considering intellectual capital as a moderator. The results indicate a positive effect of audit size and top 20 shareholders while a negative of insider shareholding and board independence on Tobin’s Q, ROE, and ROA. Additionally, for Tobin’s Q, institutional shareholding and CEO duality, a positive effect while negative of board size is found. While the negative effect of institutional shareholdings and CEO duality and the positive of board size is found in the case of ROE, ROA and intellectual capital moderation is found for all performance measures. The findings are consistent with stewardship and agency theory. The empirical outcomes emphasize the importance of intellectual capital for policymakers and regulators considering it rewarding activity for shareholder wealth maximization.